Answer:
a)
![f^(-1) (x) = (1)/(2) Cos^(-1) ((x-1)/(3) ) +(3)/(2)](https://img.qammunity.org/2021/formulas/mathematics/college/tvxx754ge0krtw39lf44envfiucil14twp.png)
The inverse of given function
![f^(-1) (x) = (1)/(2) Cos^(-1) ((x-1)/(3) ) +(3)/(2)](https://img.qammunity.org/2021/formulas/mathematics/college/tvxx754ge0krtw39lf44envfiucil14twp.png)
Explanation:
Step(i):-
Given function f(x) = 3 cos (2 x -3) + 1
Let y = f(x) = 3 cos (2 x -3) + 1
y = 3 cos (2 x -3) + 1
⇒ y - 1 = 3 cos (2 x -3)
⇒
![cos ( 2 x - 3 ) =(y -1)/(3)](https://img.qammunity.org/2021/formulas/mathematics/college/opofi5e8n3urwav10edzr2wo27yjnbxx5r.png)
⇒
![cos ^(-1) ( cos (2 x - 3)) = Cos^(-1) ((y-1)/(3) )](https://img.qammunity.org/2021/formulas/mathematics/college/tfgfl9d2hqobzxcp9hf2hpt9kac2kqm9dj.png)
We know that inverse trigonometric equations
cos⁻¹(cosθ) = θ
![2 x - 3 = Cos^(-1) ((y-1)/(3) )](https://img.qammunity.org/2021/formulas/mathematics/college/9odaofr3rq02fd7ai1psnboa0znwb7mzxk.png)
![2 x = Cos^(-1) ((y-1)/(3) ) +3](https://img.qammunity.org/2021/formulas/mathematics/college/264ip7brs0wl9znnxv3jp4y830bgt6aaff.png)
![x = (1)/(2) Cos^(-1) ((y-1)/(3) ) +(3)/(2)](https://img.qammunity.org/2021/formulas/mathematics/college/nro8qoru4e0096zq3aft6ot2nq1jrjymux.png)
Step(ii):-
we know that y= f(x)
The inverse of the given function
![x = f^(-1) (y)](https://img.qammunity.org/2021/formulas/mathematics/college/bvlrgh0ixzb0d637wbrgxuddztjln7k3mk.png)
![f^(-1) (y) = (1)/(2) Cos^(-1) ((y-1)/(3) ) +(3)/(2)](https://img.qammunity.org/2021/formulas/mathematics/college/na70nht3o86o26j1xljqdjhsi53c0fycxk.png)
The inverse of given function in terms of 'x'
![f^(-1) (x) = (1)/(2) Cos^(-1) ((x-1)/(3) ) +(3)/(2)](https://img.qammunity.org/2021/formulas/mathematics/college/tvxx754ge0krtw39lf44envfiucil14twp.png)
conclusion:-
The inverse of given function